Development of bioorganic fertilizer containing Amphinema GanoEF2 and evaluation of its effectiveness in promoting oil palm growth and suppressing Ganoderma boninense - Mohd Kamel, Siti Hairunnisa (2014)
The oil palm, Elaeis guineensis is the most important crop in Malaysia which producing an average palm oil yields approximately 4 tonnes per hectare per year. Basal stem rot (BSR) disease which is caused by Ganoderma boninense is the most serious disease that infected oil palm. Recently, the control of BSR has been focused on the use of biocontrol agent such endophytic fungi. Therefore, the objectives of this study were; 1) to formulate bioorganic fertilizer containing Amphinema GanoEF2, 2) to evaluate the effectiveness of bioorganic fertilizer containing Amphinema GanoEF2 in enhancing growth of oil palm seedlings, and 3) to determine the efficacy of bioorganic fertilizer containing Amphinema GanoEF2 for controlling Ganoderma disease in oil palm seedlings. Amphinema GanoEF2 was isolated from symptomless root of oil palm by Malaysian Palm Oil Board (MPOB) and was found to have an antagonistic activity against G. boninense. Two types of bioorganic fertilizers; empty fruit bunch (EFB) and Real Strong bioorganic fertilizer (RSBF) were incorporated into powder formulation containing Amphinema GanoEF2. The products were prepared in five different ratios of vermiculite containing Amphinema GanoEF2 to bioorganic fertilizers (EFB/RSBF) (10:50 g, 20:40 g, 30:30 g, 40:20 g and 50:10 g). The shelf life of Amphinema GanoEF2 and efficacy towards G. boninense were determined by in vitro study during eight months of storage. Ratio of 30 g of vermiculite Amphinema GanoEF2 to 30 g of EFB and 50 g of vermiculite Amphinema GanoEF2 to 10 g of RSBF recorded the highest fungal colonies of Amphinema GanoEF2 among other ratios with the percentage inhibition of radial growth (PIRG) against G. boninense recorded at 50% and 52%, respectively. The chosen ratios were used to prepare the product and were evaluated in nursery trials for oil palm growth and controlling BSR disease. The application of bioorganic EFB Amphinema GanoEF2 (T2) and bioorganic RSBF Amphinema GanoEF2 (T3) on oil palm seedlings has significantly increased the plant height, frond length, number of frond, number of leaflets, stem diameter, leaf area index and chlorophyll content as compared with untreated seedlings (T1). The total biomass of T2 (109.15 g) and T3 (112.03 g) seedlings have a significant difference compared with T1 seedlings after eight months of treatments with the value of relative growth rate (RGR) for T1, T2 and T3 seedlings at 1.44 g/month, 1.49 g/month and 1.52 g/month, respectively. The efficacy of bioorganic EFB Amphinema GanoEF2 (T3) and bioorganic RSBF Amphinema GanoEF2 (T4) to control Ganoderma disease were evaluated and found that T3 and T4 seedlings recorded a significant reduction of BSR disease. The percentage of disease incidence (DI) for T3 and T4 seedlings were only 50% and 40%, respectively, compared with T1 seedlings which recorded 80% of DI. The disease severity index of foliar, root and bole (DSIF, DSIR, DSIB), dead seedlings (DS) and area under disease progress curve (AUDPC) also showed significant difference between treated seedlings (T3 and T4) with untreated seedlings (T2). Both bioorganic EFB Amphinema GanoEF2 and bioorganic RSBF Amphinema GanoEF2 were enhanced the growth of oil palm seedlings and were capable in reducing the BSR infection.